2019
DOI: 10.1155/2019/5392945
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Painful Ophthalmoplegic Neuropathy and Oculomotor Nerve Schwannoma: A Pediatric Case Report with Long-Term MRI Follow-Up and Literature Review

Abstract: Background Recurrent painful ophthalmoplegic neuropathy (RPON), previously known as ophthalmoplegic migraine (OM), is an uncommon disorder with repeated episodes of ocular cranial nerve neuropathy associated with ipsilateral headache. The age of presentation is most often during childhood or adolescence. MRI has a central role in the assessment of the RPON, especially to distinguish orbital, parasellar, or posterior fossa lesions that mimic symptoms of RPON. Actually, oculomotor nerve tumors may be masquerade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 42 publications
1
21
0
1
Order By: Relevance
“…However, the increased thickening of the oculomotor nerve observed after 9 years of RPON attacks may serve as evidence in support of the tumor theory. This hypothesis extends the inflammatory theory, proposing that repeated bouts of inflammation may lead to cycles of demyelination and remyelination of the affected nerve, and such a process may encourage the transformation of Schwann cells to schwannoma (5). Yet, as Kim et al, Akimoto et al, and Shin et al, have proposed, follow-up surveillance via MRI is required to exclude tumors, especially in patients with suspected RPON with persistent post-contrast enhancement during times of remission (10,11,20).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, the increased thickening of the oculomotor nerve observed after 9 years of RPON attacks may serve as evidence in support of the tumor theory. This hypothesis extends the inflammatory theory, proposing that repeated bouts of inflammation may lead to cycles of demyelination and remyelination of the affected nerve, and such a process may encourage the transformation of Schwann cells to schwannoma (5). Yet, as Kim et al, Akimoto et al, and Shin et al, have proposed, follow-up surveillance via MRI is required to exclude tumors, especially in patients with suspected RPON with persistent post-contrast enhancement during times of remission (10,11,20).…”
Section: Discussionsupporting
confidence: 60%
“…As for the tumor pathogenesis, it has been reported that transient or recurrent oculomotor nerve deficits may be the primary manifestation in some cases of cranial nerve schwannoma (10). Recently, Petruzzelli et al have reported a case of a 16-year-old boy with a diagnosis of OM initially but which turned out to have the presentation of a schwannoma after 7year follow-up (5). In her review, three cases of schwannoma of the affected nerve had been reported, which included a long history of follow-up, and only one was histologically proven (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the relationship between RPON and schwannoma. As proposed by Petruzzelli et al (15), we are performing a long-term follow-up at our institute in order to prevent any complications.…”
Section: Discussionmentioning
confidence: 99%
“…Egyik elmélet szerint a tumor intermittensen olyan kémiai anyagokat bocsájt ki már akkor is, amikor imagisztikailag még nem detektálható, amelyek stimulálják a trigeminus receptorait, ami migrénes fejfájáshoz vezet, így a RPON a tumor kezdeti megnyilvánulásának tekinthető [32,34]. A másik hipotézis szerint a RPON hátterében álló visszatérő gyulladás sorozatos demyelinisatiohoz és remyelinisatiohoz vezet, amelyek elindíthatják a Schwann-sejtek proliferációját és átalakulását schwannomává, így ez a tumor a RPON hosszútávú komplikációjának tekinthető [35].…”
Section: Megbeszélésunclassified